Calculation of admissions for geodetic marking works taking into account the accuracy of technological processes at researches and construction of highways - YU. V. Stolbov; S. YU. Stolbova; L. A. Pronina; I. E. Starovoytov (Вестник СибАДИ, 2017)
Calculations of admissions for geodetic marking works taking into account the accuracy of their technological processes at researches and construction of highways are given. Calculations of admissions for geodetic control of elevation marks at the device of constructive layers of the bases and coverings of road clothes are executed. These calculations admissible values of amplitudes of elevation marks of surfaces of the bases and coverings were assumed as a basis. By an initial basis at calculations of admissions on detailed breakdown, carrying out of marks of pickets on the route of highways and a prolozheniye of the leveling courses on the route, are accepted, the tolerances of high-rise marks from the design regulated in normative documents.